Supraclavicular Block Using Ultrasonography (USG) Guidance in Ulna Radius Fractures Patients with Moderate Mitral Regurgitation Undergoing ORIF (Open Reduction and Internal Fixation): A Case Report - Rauwelio, Alvin; I Made Dwi Pramana; Benny Supono; Ida Ayu Apsari Pradnya Niti; William Audi; I Wayan Widana (HM Publisher, 2024)
Background: Open fractures of the radius and ulna in elderly patients are conditions that require fast and appropriate treatment. Open reduction internal fixation (ORIF) is a common treatment option, but in elderly patients, general anesthesia may be high risk. Supraclavicular brachial plexus block is an effective and safe regional anesthetic option for ORIF in elderly patients. Case presentation: We report the case of a 71-year-old man with an open fracture of the left third radius and middle ulna who was planned for ORIF. The patient had comorbid hypertension and reduced left ventricular function. Supraclavicular brachial plexus block was performed using 0.5% bupivacaine (10 mL) and 2% lidocaine (10 mL). The patient did not complain of pain during the operation and recovered well. Conclusion: Supraclavicular brachial plexus block is an effective and safe regional anesthetic option for ORIF in elderly patients with open fractures of the radius and ulna.